Perancangan Rekam Medis PPTM Berbasis Android dan Mikrokontroler Menggunakan Teknologi RFID - Unang Sunarya; Junartho Halomoan; Gentra A.P. Ruswanda (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
Health is very important thing in our life. Therefore , many people who regularly check their health to know their medical history. Unfortunately the data that will be medical history is frequently lost as a result of sloppy documentation, whereas medical history of data is very important to follow up on further treatment, especially on the case of having treatment to the other place or doctor. This research created a tool that can store and read data of the patient's identity of communicable diseases ( PPTM ) including health history . The data of health was stored in an RFID chip (RFID Tags) so that data could be flexibly held by subject of PPTM. When he/she went to the doctor , the doctor could check the medical history of the subject of PPTM by reading RFID Tags carried by subject of PPTM through an RFID reader and displayed it on android device. The result shows that the device is able to work with a maximum distance data transmission as far as 28.60 meters.